In Search of a Dose: The Functional and Molecular Effects of Exercise on Post-stroke Rehabilitation in Rats - Li, Fengwu; Geng, Xiaokun; Huber, Christian; Stone, Christopher; Ding, Yuchuan (Frontiers in Cellular Neuroscience, 2020)
Although physical exercise has been demonstrated to augment recovery of the post-stroke brain, the question of what level of exercise intensity optimizes neurological outcomes of post-stroke rehabilitation remains unsettled. In this study, we aim to clarify the mechanisms underlying the intensity-dependent effect of exercise on neurologic function, and thereby to help direct the clinical application of exercise-based neurorehabilitation. To do this, we used a well-established rat model of ischemic stroke consisting of cerebral ischemia induction through middle cerebral artery occlusion. Ischemic rats were subsequently assigned either to a control group entailing post-stroke rest, or to one of two exercise groups distinguished by the intensity of their accompanying treadmill regimens. After 24 h of reperfusion, exercise was initiated. Infarct volume, apoptotic cell death, and neurological defects were quantified in all groups at 3 days, and motor and cognitive function were tracked up to day 28. Additionally, Western blotting was used to assess the influence of our interventions on several proteins related to synaptogenesis and neuroplasticity (growth-associated protein 43, microtubule-associated protein, postsynaptic density-95, synapsin I, hypoxia inducible factor-1α, brain-derived neurotrophic factor, nerve growth factor, tyrosine kinase B, and cAMP response element binding protein). Our results were in equal parts encouraging and surprising. Both mild and intense exercise significantly decreased infarct volume, cell death, and neurological deficits. Motor and cognitive function, as determined using an array of tests such as beam balance, forelimb placing, and the Morris water maze, were also significantly improved by both exercise protocols. Interestingly, while an obvious enhancement of neuroplasticity proteins was shown in both exercise groups, mild exercise rats demonstrated a stronger effect on the expressions of Tau (p<0.01), brain-derived neurotrophic factor (p<0.01), and tyrosine kinase B (p<0.05). These findings contribute to the growing body of literature regarding the positive effects of both mild and intense long-term treadmill exercise on brain injury, functional outcome, and neuroplasticity. Additionally, the results may provide a base for our future study regarding the regulation of HIF-1α on the BDNF/TrkB/CREB pathway in the biochemical processes underlying post-stroke synaptic plasticity.